Brachysira aristidesii sp. nov. (Bacillariophyceae, Brachysiraceae): a new species from oligotrophic and mesotrophic tropical reservoirs in southeastern Brazil - Zorzal-Almeida, Stefano; Rodrigues Bartozek, Elaine C. [UNESP]; Morales, Eduardo A.; Bicudo, Denise C. [UNESP] (Magnolia Press, 2020)
A new diatom species, Brachysira aristidesii sp. nov., is described from three oligotrophic and mesotrophic reservoirs in Piracicaba River basin, State of Sao Paulo, Brazil. Descriptions are based on light and scanning electron microscopy. The new species is mainly characterized by rhombic-lanceolate valves with strongly capitated ends, filiform and straight raphe, narrow and linear axial area, slightly radiate striae and transapically elongated areolae. It is compared to Brachysira microcephala, B. silvicola, B. vitrea, B. neoexilis and Nupela brachysiroides. Our findings suggest that Brachysira aristidesii is a species mainly associated to high water transparency, low to moderate conductivity, slightly acidic and low nutrient environments.
Keywords: Autecology; diatom; inland waters; surface sediment; taxonomy